(untitled) (Journal of Economic Research & Business Administration, 2016)
The present stage of development is characterized by standardizing products and services commonality. An effective way to attract attention, to keep the commitment and loyalty of client – is the individualization of products and companies in his mind, it is possible on the basis of correct positioning. Positioning as a result of effective collaboration becomes a major factor in the continuity of the company’s existence in the market. For advanced enterprise hotel services success in the competition, not least associated with the implementation of positioning strategies. In this context, this article deals with the importance of the positioning of the hotel enterprises, methods of differentiation, the process of strategies development. It was carried out the analysis of the competitive advantages and positioning of some Kazakhstan’s hotel enterprises in modern conditions.